2019
DOI: 10.1186/s13068-019-1473-0
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative image analysis pipeline for the characterization of filamentous fungal morphologies as a tool to uncover targets for morphology engineering: a case study using aplD in Aspergillus niger

Abstract: Background Fungal fermentation is used to produce a diverse repertoire of enzymes, chemicals, and drugs for various industries. During submerged cultivation, filamentous fungi form a range of macromorphologies, including dispersed mycelia, clumped aggregates, or pellets, which have critical implications for rheological aspects during fermentation, gas/nutrient transfer, and, thus, product titres. An important component of strain engineering efforts is the ability to quantitatively assess fungal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 50 publications
4
58
0
Order By: Relevance
“…3). Consistent with the previous studies [31][32][33][34], Tet-on system is a useful method to functionally analyze essential genes, enabling analyses of null, loss-of-function, and over-expression in a single strain by addition of the inducer Dox. After co-transformation, ten randomly selected primary transformants were subcultured on MM plates, MM supplemented with 20 µg/mL Dox and MM supplemented with uridine.…”
Section: Generation Of a Pyrg Conditional Expression Mutant In A Nigersupporting
confidence: 69%
“…3). Consistent with the previous studies [31][32][33][34], Tet-on system is a useful method to functionally analyze essential genes, enabling analyses of null, loss-of-function, and over-expression in a single strain by addition of the inducer Dox. After co-transformation, ten randomly selected primary transformants were subcultured on MM plates, MM supplemented with 20 µg/mL Dox and MM supplemented with uridine.…”
Section: Generation Of a Pyrg Conditional Expression Mutant In A Nigersupporting
confidence: 69%
“…4a and a summary of growth phenotypes given in Table 2. Additionally, pellet Euclidian parameters (maximum diameter, area, solidity, and aspect ratio, see methods) were quantified using the automated Morphology of Pelleted and Dispersed growth (MPD) image analysis pipeline [37] and used to determine the dimensionless morphology number (MN [38]), which generates a value between 0 (a theoretical one-dimensional line) and 1 (a perfect round sphere, Fig. 4b).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Jeennor et al [69] reported that an A. oryzae mutant defective in the ags1 (agsB) gene showed an increase in lipid productivity in submerged flask and 5-L reactor cultivation in comparison with the parental strain. Recently developed software enables automatic characterization of hyphal macromorphology including hyphal area, pellet diameter, aspect ratio, and solidity [70]. Applying this software for characterization of α-1,3-glucan mutant hyphae could be a new approach to understand the relationship between fungal cell wall composition and morphogenesis.…”
Section: α-13-glucanmentioning
confidence: 99%